Effectiveness of virtual reality-based interventions in rehabilitation management of breast cancer survivors: protocol of a systematic review and meta-analysis. Issue 2 (16th February 2022) - Bu, Xiaofan; Ng, Peter H F; Chen, Qi; Cheng, Andy S K; Xu, Wenjing; Tong, Ying; Tang, Qingping; Liu, Xiangyu
Abstract : Introduction: Breast cancer is the leading cause of global cancer incidence and represents 11.7% of all new cancer cases. However, breast cancer survivors (BCS) suffer from many intense physical and psychological symptoms, functional deficits and adverse effects during and after treatment, significantly affecting their quality of life. Virtual reality (VR) technology uses computer technology to create an interactive three-dimensional world by visual, audio and touch simulation and is being used in breast cancer rehabilitation management. This paper reports on the protocol for a systematic review and meta-analysis exploring the efficacy of VR-based interventions in the rehabilitation management of BCS. Methods and analysis: This protocol for conducting a systematic review and meta-analysis was prepared according to the recommendations of the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols 2015 statement. Web of Science, PubMed, Embase, CINAHL, Cochrane Central Register of Controlled Trials, CNKI, Wanfang, VIP and SinoMed will be used in the search. The search will include randomised controlled trials, quasi-experimental studies and case-controlled trials published in English and Chinese. Further, the risk of bias of the studies included in the systematic review and meta-analysis will be assessed using the Cochrane risk-of-bias tool. The statistical program Review Manager V.5.3 will be used in the meta-analysis. The I² test will be used to determine statistical heterogeneity among the included studies. Ethics and dissemination: Ethics approval will not be needed because the data to be used in this systematic review and meta-analysis will be extracted from published studies. The systematic review and meta-analysis will focus on whether VR-based interventions are effective in the rehabilitation management of BCS. It will be disseminated by publication in a peer-reviewed journal. PROSPERO registration number: CRD42021250727.